The Influence of Project Based Learning (PjBL) Learning Model on Social Studies Learning Outcomes of Grade IV Students at UPTD SD Negeri 125549 - Ompusunggu, Elly Fitri; Sirait, Esti; Barus, Maria (Lembaga Riset Mutiara Akbar, 2025)
This study aims to determine the Effect of Using the Project Based Learning (PjBL) Learning Model on the Learning Outcomes of Grade IV Students at UPTD SD Negeri 125549. The design of this study was pre-Experimental with the form of One-Group Pretest-Posttest Design. The sample of this study was all students of grade IV-B UPTD SD Negeri 125549 totaling 20 students. The hypothesis in this study is, (1) there is an effect of the application of the Project Based Learning (PjBL) learning model on the learning outcomes of grade IV students at UPTD SD Negeri 125549 (Ha), (2) there is no effect of the application of the Project Based Learning (PjBL) learning model on the learning outcomes of grade IV students at UPTD SD Negeri 125549 (Ho). Data collection was carried out by giving pretest and posttest questions to students. Data were analyzed using the normality test (Shapiro-Wilk) and the score increase test (N-Gain). The results showed that the average pretest score of students was 43 with a completion rate of 20%, which increased to 83 with a completion rate reaching 90% in the posttest. The results of the normality analysis showed that the pretest data had a significant value of 0.135 more than 0.05 and the posttest data had a significant value of 0.349 more than 0.05 so that the results of the normality analysis had normally distributed data, and an average N-Gain score of 0.7163 showed a high increase category, with learning effectiveness of 71.6262%.